Clinical Characteristics of Diabetic Patients with Diabetic Retinopathy - Blum, Arnon; Socea, Dorina (Journal of Nutritional Therapeutics, 2013)
Background: Proliferative diabetic retinopathy is a consequence of retinal ischemia due to capillary occlusion resulting from damage to the retinal endothelium, and is associated with increased risk of cardiovascular morbidity and mortality. Methods: We randomly assigned seventy three patients with DM type II and grouped them according to their retinal proliferative disease (Group A - 25 patients [12 males], mean age 62.8±10.8 years, no diabetic retinopathy; Group B - 25 patients [19 males], mean age 61.9±9.4 years, non-proliferative retinopathy; and Group C - 23 patients [13 males], mean age 59.2±10.3 years, proliferative retinopathy). Twenty three healthy subjects (14 males; mean age 44.3±11.6 years) served as the control group. We studied their retinal vasculopathy status, height, weight, body mass index (BMI), waist circumference, age, endothelial function (flow mediated diameter [FMD%] percent change) and their peripheral artery disease (ankle brachial index [ABI]). Results: A significant difference was found between the duration of length of DM type II between patients without retinopathy [group A] (9±6 years) and patients with non-proliferative retinopathy [group B] (17±9 years) (p=0.001). No difference in length of diabetes was observed between patients with non-proliferative retinopathy [group B] and patients with proliferative retinopathy [group C] (19±6 years) (p=0.30). A significant difference was observed in HgA1C% between group A (7.1±2.7%) and group B (8.5±1.5%) (p=0.02). No such difference was noted between group B and group C (8.5±1.6%) (p=0.98). Only 6 patients (out of 23) used insulin treatment in group A compared with 16 group B (out of 25) and 17 in group C (out of 25) (p=0.004). All three groups of diabetic patients were older (62.8±10.8, 61.9±9.4, 59.2±10.3 years, respectively) than volunteers (44.3±11.6 years) (p≤0.001), had a lower stature (1.65±0.09, 1.68±0.07, 1.65±0.09 meters, respectively) compared with controls (1.73±0.08 meters) (p≤0.05), had a larger waist circumference (110.04±14.17, 108.88±13.00, 109.30±13.49 cm, respectively) than controls (93.43±11.66 cm) (p≤0.001), and larger BMIs (30±6, 29±4, 30±5) compared with controls (25±4) (p≤0.001). All diabetic patients had severe endothelial dysfunction measured by FMD% (-1.9±7.4, -3.3±9.2, -3.1±6.6 %, respectively) compared with the control group (16.5±7.5%) (p≤0.001). ABI was within normal range in all patient (0.97±0.18, 1.14±0.24, 1.03±0.28, respectively), and in volunteers (1.06±0.18) (p≥0.05). There was no significant change within the 3 subgroups of diabetic retinopathy patients in age, height, weight, BMI, or FMD%. Conclusions: All patients with DM type II had severe endothelial dysfunction, higher BMIs, lower statures, larger waist circumferences; however they all had normal ABIs